STUDY ON THE TESTING OF POWER BREAKERS (PMT) IN THE 150 KV TRANSFORMER BAY AT THE PANAKKUKANG SUBSTATION - Salam, Fardian; Fathahillah, Fathahillah; Zulhajji, Zulhajji (Fakultas Teknik Universitas Negeri Makassar, 2024)
The Circuit Breaker (PMT) plays a very important role in the substation system because the PMT is the equipment responsible for disconnecting the load current during a disturbance. This study aims to determine the results of insulation resistance testing, contact resistance testing, and simultaneity of the Circuit Breaker (PMT), evaluate the quality of the PMT, and determine the results of the NGR (Neutral Grounding Resistor) testing at the Panakkukang Substation. This research employs a quantitative method using an ex post facto research design. The research was conducted at PT. PLN (Persero) Panakkukang Substation, with the object being the 150 kV transformer bay Circuit Breaker (PMT). The results obtained from this study show that the insulation materials and contact components of the Circuit Breaker installed in transformer bay 2 are still in good and safe condition. The Circuit Breaker can trip according to normal simultaneity performance. The quality of the PMT is still in safe and operational condition, and the NGR (Neutral Ground Resistor) test results for transformer bay 2 indicate that it is still in good and safe condition.